Real-time fuzzy-pid synchronization of memristor-based chaotic circuit using graphical coded algorithm in secure communication applications - Guler, Hasan (Iop Publishing Ltd, 2022)
The main goal of this study is to implement real-time synchronization of a memristor-based chaotic circuit for secure communication on LabVIEW virtual instrument environments. Memristors can be used in chaotic circuits because of their nonlinear behavior. In this paper, an application for secure communication systems is proposed by using the chaotic property of the memristor. Phase portraits, Lyapunov exponential spectrum, and bifurcation diagrams of the memristor-based chaotic circuit were investigated. A Fuzzy-PID controller was used for master-slave synchronization of memristive chaotic circuit and in secure communication application, three images were also used for encryption and decryption. NI 6251 DAQ card was used to obtain real-time results. Information entropy values, correlation coefficients (CC), peak signal to noise ratio (PSNR), structural similarity index (SSIM), correlation coefficients for the horizontal, vertical and diagonal directions from the three encrypted images, number of pixels change rate (NPCR) and unified average changing intensity (UACI) are calculated to test encryption/decryption performance in the designed system. The results obtained from real-time applications and simulations prove that memristor-based chaotic circuits can be used in secure communication systems where privacy is important.
Keywords: memristor; chaotic dynamics; fuzzy; PID; synchronization